The effect of nonhuman's external regulation on children's responses to detect children with developmental problems (DP) associated with the natural development of self-regulation during learning tasks - Agina, A.; Kommers, Petrus; Steehouder, M. (Elsevier, 2012)
The present study sought to examine the effect of the nonhuman's external regulation on children's responses during learning tasks to detect children with developmental problems (DP) associated with the natural development process of self-regulation. The material was an isolated, computer-based learning system that acts as a standalone learning environment and used by 100 preschool children, which were randomly selected from ten preschools without revising their medical files. Participants were classified by the system itself during learning progression in three essential groups based on Aginian's zone of children regulation (ZCR), which is "the equilibrium point in the self-regulation's development process that controls the child to be either a self-Vygotskyian's learner, self-Piagetian's learner, or self-Aginian's learner during learning tasks" (Agina, Kommers, & Steehouder, 2011d). The results showed that the preschool children can spontaneously do diagnostic tests during learning tasks and the nonhuman external regulator was able to analysis children's responses that, in turn, used for detecting those children with DP. This result was practically confirmed by revising all children's medical files that matched the final judgment of the nonhuman external regulator. However, the results confirmed that the natural development of self-regulation was fluctuated among three paradoxical views (Vygotskyian vs. Piagetian vs. Aginian). © 2011 Elsevier Ltd. All rights reserved.